The reformation of prophecy early modern interpretations of the prophet and Old Testament prophecy - Pak, G. Sujin 1971- (Oxford Oxford University Press USA - OSO, 2018)
The Reformation of Prophecy illuminates the significant shifts in the Protestant reformers' engagement with the prophet and biblical prophecy-shifts from advancing the priesthood of all believers to strengthening Protestant clerical identity and authority to operating as a site of polemical-confessional exchange concerning right interpretations of Scripture.
Cover -- The Reformation of Prophecy -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- 1. Prophecy and the Priesthood of All Believers -- 2. Prophecy and the Radicals: Rethinking Prophecy and the Prophet Contra the Radicals -- 3. Prophecy and the Pastoral Office: Luther and Zwingli -- 4. Prophecy and the Teaching Office: Bullinger and Calvin -- 5. The Prophet, Prophecy, and the Pastoral Office in the Next Generation -- 6. Old Testament Prophecy and Protestant Conceptions of Sacred History -- 7. Later Lutheran, Swiss Reformed, and Calvinist Readings of Sacred History in the Old Testament Prophets -- 8. Christological Exegesis and the Interpretation of Metaphors in Old Testament Prophecy -- Conclusion -- Select Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Protestant churches-Doctrines; Prophecy-Christianity-History of doctrines; Electronic books